Rancang Bangun Alat Pembangkit Uap Menggunakan Energi Surya - Aldiyanto; Adib Satono; Kadek Edy Susanto; Wandi Haryansa; Rival Kahfi Gama; La Hasanudin; Aminur (Piston: Jurnal Teknologi, 2022)
Renewable energy now seems to be the most sought after energy source. One of the renewable energy sources that is easy to obtain, endless, and environmentally friendly is solar energy. There are two kinds of technologies that have applying to exploit the potential of solar energy, namely thermal solar energy technology and photovoltaic solar energy technology. In this research, a generator will making that utilizes solar energy as a heat source to produce steam using reflected light from a mirror (reflector). The working principle of this tool is to use solar heat by concentrating sunlight to one point, the heat collected can be used to generate electricity in a conventional way. This technology is known as Concentrating Solar Power (CSP). The heat from this mirror reflected light will heat the water in the boiler to produce steam. The material used in this research is stainless steel because the thermal conductivity value is greater than other types of metal so that it is easier to conduct heat.